1997
DOI: 10.1164/ajrccm.155.3.9117038
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis enhances human immunodeficiency virus-1 replication in the lung.

Abstract: We investigated the in vivo effect of coinfection of Mycobacterium tuberculosis on human immunodeficiency virus type 1 (HIV-1) replication using bronchoalveolar lavage (BAL) of 11 HIV-1-infected patients with pulmonary tuberculosis and 10 patients with no lung disease. Lung segments involved with pulmonary tuberculosis had significantly elevated HIV-1 branched DNA (bDNA) levels and p24 in BAL compared with lung segments uninvolved with tuberculosis or with BAL from patients with no lung disease. The BAL viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
1
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 30 publications
7
153
1
2
Order By: Relevance
“…Macrophages in lung segments involved with tuberculosis lose C/EBP␤ expression, express another C/EBP site-binding activity, and support high level HIV-1 replication (4,5,15). As expected, PMA-treated THP-1 cells or primary macrophages infected in vitro with M. tuberculosis exhibited a type I IFN response characteristic of resting alveolar macrophages, which strongly expressed the inhibitory C/EBP␤ and suppressed HIV-1 replication (15).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Macrophages in lung segments involved with tuberculosis lose C/EBP␤ expression, express another C/EBP site-binding activity, and support high level HIV-1 replication (4,5,15). As expected, PMA-treated THP-1 cells or primary macrophages infected in vitro with M. tuberculosis exhibited a type I IFN response characteristic of resting alveolar macrophages, which strongly expressed the inhibitory C/EBP␤ and suppressed HIV-1 replication (15).…”
Section: Discussionsupporting
confidence: 64%
“…Fewer than 3 in 10 5 alveolar macrophages are infected, even in advanced AIDS (3). Opportunistic infections such as pulmonary tuberculosis markedly up-regulate HIV-1 replication in the lung and lead to mutations in the viral envelope gp120 V3 region associated with increased virulence (4).…”
Section: Differentiation Of Monocytes To Macrophages Switches the Mycmentioning
confidence: 99%
“…This may be due to increased HIV-1 replication and mutation in the lung produced by TB (3,4). Understanding the mechanisms underlying the synergistic interaction between HIV and TB may lead to improved strategies for the control of both infections (5).…”
Section: P Atients With Coinfection Of Hiv and Pulmonary Tuberculosismentioning
confidence: 99%
“…TB and HIV also interact in the lungs, the site of primary infection with M. tuberculosis. In a recently published study of HIVinfected patients with TB, researchers found that the viral load was higher in the bronchoalveolar lavage fluid from the affected versus the unaffected lung and was correlated with levels of tumor necrosis factor in bronchoalveolar fluid [21] . Researchers used V3 loop viral sequences to construct a phylogenetic tree and observed that the HIV quasispecies from the affected lung differed from those in the plasma within the same patient.…”
Section: Tb and Hiv/aidsmentioning
confidence: 99%